Poly(acrylonitrile) based ultrafiltration membranes: optimization of preparation parameters - Lohokare, Harshada R.; Bhole, Yogesh S.; Taralkar, Suyog; Kharul, Ulhas K. (Desalination, 2011)
Supported ultrafiltration (UF) membranes based on poly(acrylonitrile) were prepared while varying crucial parameters responsible for controlling membrane porosity, viz.; polymer concentration, solvent and additives in the dope solution. Insight into membrane porosity and morphology was obtained by water flux, solute rejection, bubble point, pore size distribution, SEM and AFM analyses. It was found that merely increasing polymer concentration does not necessarily reduce pore size of membranes. Among four solvents used for the dope solution preparation, N-methyl pyrrolidone was found to offer membranes with optimal combination of flux and rejection of various solutes. Some of the PAN(17) (17% w/w PAN concentration in the dope solution) membranes prepared using organic acid as the additive (citric acid, tartaric acid or maleic acid) offered 1.2-1.7 times higher flux than the membrane prepared using inorganic salt, ZnCl2 as an additive. The porosity of PAN(17) membrane prepared using CA as an additive was larger as compared to membrane prepared using ZnCl2 as an additive. Atomic force microscopy (AFM) analysis of this membrane exhibited higher surface roughness as compared to the ZnCl2 based membrane. Both these membranes exhibited bacteria (E. Coli) log reduction value (LRV) of at least 6; depicting applicability of these membrane for water disinfection. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Additive; Bacteria rejection; Poly(acrylonitrile); Pore size distribution; Ultrafiltration